White sands experiences from the outside world - Dyer, Geoff 1958- (Pantheon Books, 2016)
"From "one of our most original writers" (Kathryn Schulz) comes an expansive and exacting book--firmly grounded, but elegant, witty, and always inquisitive--about travel, unexpected awareness, and the questions we ask when we step outside ourselves. Geoff Dyer's perennial search for tranquility, for "something better," continues in this series of fascinating and seemingly unrelated pilgrimages--with a tour guide who is in fact not a tour guide at the Forbidden City in Beijing, with friends at the Lightning Field in New Mexico, with a hitchhiker picked up near a prison at White Sands, and with "a dream of how things should have been" at the Watts Towers in Los Angeles. Weaving stories about places to which he has recently traveled with images and memories that have persisted since childhood, Dyer tries "to work out what a certain place--a certain way of marking the landscape--means; what it's trying to tell us; what we go to it for." He takes his title from Gaugin's masterwork, and asks the same questions: Where do we come from, what are we, where are we going? The answers are elusive, hiding in French Polynesia, where he travels to write about Gaugin and the lure of the exotic; at the Museum of Fine Arts in Boston, where he goes to see the masterpiece in person only to be told it is traveling; and in Norway, where he and his wife journey to see, but end up not seeing, the Northern Lights. But at home in California, after a medical event that makes Dyer see everything in a different way, he may finally have found what he's been searching for"--